Diagnosis and treatment of polycystic ovary syndrome - Ronelsys Martínez Martínez; Raúl González Salas; Ariel Leonardo Alarcón Vela; Diana Sofía Iglesias Espín (Medisur)
Polycystic ovary syndrome is an endocrine-genetic-gynecological disorder that mainly affects women of childbearing age, with manifestations of hyperandrogenism and infertility in early stages of life. This work aims to describe the diagnosis and treatment of polycystic ovary syndrome whose pathophysiology has not been fully understood, hence its diagnosis continues to be by exclusion. The Rotterdam consensus criteria have managed to improve diagnostic uniformity; however, an individualized diagnosis is necessary, which must include the study of the morphology of the ovaries. Although the literature suggests the association of this entity with the presence of obesity, insulin resistance and hyperinsulinism, they are not currently included as part of the diagnostic criteria. Treatment includes changes in lifestyle, together with inhibitors of androgen production by the ovaries, inhibitors of androgen action and insulin sensitizers; It will be established according to the patient´s reproductive interests.